IMPLEMENTATION OF MAQĀṢID AL-SYARĪ'AH IN ISLAMIC RELIGIOUS EDUCATION FOR THE SOCIAL RECOVERY OF FLOOD VICTIMS - Muhammad Faisal Azmi (Journal of International Islamic Law, Human Right and Public Policy, 2026)
This study discusses the implementation of Maqāṣid al-Syarī'ah in Islamic Religious Education (PAI) as a social recovery effort for flood victims. Flood disasters not only cause physical and economic damage, but also impact the psychological, social, and spiritual conditions of the affected community. This study aims to analyze the role of Maqāṣid al-Syarī'ah values in PAI learning to strengthen social solidarity, mental resilience, and post-disaster community recovery. The research method used is qualitative research with a descriptive approach through literature study and conceptual analysis of literature related to Maqāṣid al-Syarī'ah, Islamic education, and social recovery of disaster victims. The results of the study indicate that the implementation of the values of protecting religion (ḥifẓ al-dīn), soul (ḥifẓ al-nafs), reason (ḥifẓ al-'aql), and wealth (ḥifẓ al-māl) in Islamic Religious Education (PAI) can build social awareness, strengthen empathy, and encourage community participation in the social rehabilitation process for flood victims. Thus, Islamic Religious Education based on Maqāṣid al-Syarī'ah has a strategic contribution in shaping holistic and sustainable social recovery.